When Faculty Downsizing and Student Success Collide - Yasenka Peterson; Jessica Nelson; Marcee Everly; Kathyrn Berlin; Peggy Weber (Academic Chairpersons Conference Proceedings, 2018)
This session will discuss increasing challenges chairpersons and associate deans’ experience when faced with decreasing or limited faculty resources and how this ultimately impacts student success. Opportunities and best practices related to working together as a cohesive leadership team, increasing on time graduation rates and course scheduling will also discussed.
Keywords: Student and faculty success; workload; academic leadership; challenges in higher learning; faculty time; faculty shortages.